Efficient location-based conditional privacy-preserving authentication scheme for vehicle ad hoc networks. (March 2017) - Wu, Libing; Fan, Jing; Xie, Yong; Wang, Jing; Liu, Qin
Due to the real-time requirement of message in vehicle ad hoc networks, it is a challenge to design an authentication for vehicle ad hoc networks to achieve security, efficiency, and conditional privacy-preserving. To address the challenge, many conditional privacy-preserving authentication schemes using bilinear pairing or ideal tamper-proof device have been proposed for vehicle ad hoc networks in recent years. However, the bilinear pairing operation is one of the most complex cryptographic operations and the assumption of tamper-proof device is very strong. In this article, an efficient location-based conditional privacy-preserving authentication scheme without the bilinear pairing and tamper-proof device is proposed. Compared with the most recently proposed authentication schemes, the proposed scheme markedly decreases the computation costs of message signing and message verification phase, while satisfies all security requirements of vehicle ad hoc networks and provides conditional privacy-preserving.